تحقيق القول في جواز دفع القيمة في الزكاة: دراسة فقهية وأصولية - Aldershewi, Amer Abdulraouf; al-Nahari, Ameen Ahmad Abdullah Qasem; Abdul Rahman, Noor Naemah (Jurnal Fiqh, 2016)
There are differences among schools of thoughts and Muslim jurists with regard to the payment of Zakat whether by what is stated in the shariah texts or by its value. This article describes the differences in views and elaborates the causes. This article is a library research where main data are obtained from books written by those scholars. Inductive analysis is used in analyzing the data. The findings of this research show that one of the causes that led to different views and schools of thoughts whether the payment of Zakat should be by ayn al-zakat or according to its value, whether it is ta’abbudi or ma’qul ama’na. Secondly, it is recommended to study the two different views in order to determine which is more beneficial to the needy.